2013
DOI: 10.2989/16085914.2012.758082
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterisation in interspecific and intergeneric hybrids of the clariid catfishesHeterobranchus longifilis,Clarias gariepinusandClarias anguillarisin Nigeria

Abstract: Thirty-nine morphometric and five meristic comparisons were carried out on 12-month-old interspecific and intergeneric hybrids of the African clariid catfishes Heterobranchus longifilis, Clarias gariepinus and Clarias anguillaris from experimental earthen ponds in Nigeria. Canonical discriminant analysis accounted for 89.4% of the variations, with eigenvalues of 151.69 and 9.06, respectively, the highest loading in the two axes coming from only 12 variables. A re-analysis based on those 12 variables revealed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“… 27 and Akinwande et al . 2 , had earlier concluded that the display of intermediate phenotypic characteristics in the ♀ C. gariepinus × ♂ Heterobranchus longifilis (V.) hybrid was an indication of true hybridization. Hence, it is thought that they resulted from the fusion of the genetic material of both parents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 27 and Akinwande et al . 2 , had earlier concluded that the display of intermediate phenotypic characteristics in the ♀ C. gariepinus × ♂ Heterobranchus longifilis (V.) hybrid was an indication of true hybridization. Hence, it is thought that they resulted from the fusion of the genetic material of both parents.…”
Section: Resultsmentioning
confidence: 99%
“…
Figure 2 Morphological landmarks points for ( A ) typical pure Clarias gariepinus /Clarias-like Clariothalmus ( B ) Panga-like Clariothalmus ( C ) typical Pangapinus/ Pangasianodon hypophthalmus . Landmark points are; Snout 1 , origin of dorsal fin 2 , posterior end of the dorsal fin 3 , dorsal attachment of the caudal fin to the tail 4 , ventral attachment of the caudal fin to the tail 5 , posterior end of the anal fin 6 , origin of the anal fin 7 , origin of the pelvic fin 8 , origin of the pectoral fin 9 and the posterior point of the eye 10 .
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation